P-368 Serum progesterone on the day of embryo transfer in stimulated cycles does not correlate with pregnancy outcomes. (30th June 2022) - Rozen, G; Rogers, P; Polyakov, A
Abstract: Study question: Is the chance of positive hCG, clinical pregnancy or live birth in a fresh embryo transfer (ET) IVF cycle, affected by day of transfer serum progesterone (P4) level? Summary answer: There is no correlation between P4 level on the day of ET and pregnancy outcomes. What is known already: Data from studies of frozen–thawed embryo transfer cycles suggest that low as well as high P4 levels during the mid-luteal phase may decrease the chance of pregnancy. The altered P4 pattern may disrupt the endometrial maturation leading to asynchrony between embryonic development and endometrial receptivity, thereby, compromising implantation and early development of pregnancy. Study design, size, duration: A monocentric retrospective study of prospectively collected data, of women undergoing IVF or ICSI treatment July 2019-July 2020, and having a fresh day 5 single embryo transfer (SET). 825 first and second stimulation cycles were included. Patients underwent a GnRH-antagonist protocol and were triggered for final oocyte maturation with hCG (Ovidrel R ). All patients received vaginal luteal support. The study population was unselected, treated with the unit's usual stimulation protocols, representing an everyday patient cohort. Participants/materials, setting, methods: Serum P4 levels on the day of ET were correlated with positive hCG, clinical pregnancy (CP) and live birth (LB) rates. Based on previously defined P4 thresholds, patients were divided into four P4 groups based on serum levels (P4<150 nmol/l, P4 150–250 nmol/l, P4 251–400 nmol/l and P4>400 nmol/l). The data was further interrogated using additional P4 cut offs, to confirm that there were no discernible differences based on P4 levels. Main results and the role of chance: There was no level of P4 below or above which the chance of pregnancy was consistently reduced. The chance of a positive hCG-test in the whole cohort was 51%, (95% CI: 47.1-54) following blastocyst transfer and was not different across the four groups (50, 48.2, 51.1, 52%, P = 0.88). Likewise, there was no difference in CP 41.8% (CI 38.4-45.3%) and LB 30.4% (27.3-33.7%), between the four groups. No negative association between P4 and chance of pregnancy when the other thresholds, described above, were applied. All estimates were adjusted for maternal age, maternal BMI, eggs retrieved and number of eggs fertilised, with the outcome remaining unchanged. Limitations, reasons for caution: The finding of no difference in pregnancy outcomes across P4 ranges in this study, only applies to fresh blastocyst transfer IVF cycles, using hCG trigger and vaginal LPS, and should be corroborated in future clinical trials. Also, there is possible inaccuracy in P4 levels due to diurnal variability. Wider implications of the findings: Future studies are necessary to explore the diurnal variability, and its possible contribution to these results. Trial registration number: retrospective study, institutional ethics approval